The Traditional Dusun Community's Worldview on Nature Conservation through Rice Cultivation (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
The traditional Dusun community believes in the existence of a creator and the created. All creations in the universe need to be kind to each other for the purpose of balance and harmony in nature. The Dusun community believes that the natural disasters that occur on the slopes of Mount Kinabalu are the result of human negligence of other inhabitants of nature, especially those that are involved in the exploration of agricultural land. This study aims to identify the practices and beliefs of the traditional Dusun community in preserving the environment through rice cultivation activities. This qualitative study used semi-structured interviews and direct observation of rice cultivation activities in three villages near the slopes of Mount Kinabalu, Sabah. The result showed the existence of elements of practices and beliefs in the phases of land clearing, planting, and harvesting rice. Ritual ceremonies such as magawoi, pobobor do boros, madsalud, pasalakoi bambarayon, and so on are aimed at beseeching Kinorohingan and good spirits to bless the agricultural land, grow rice, and provide sufficient yields to farmers. The forms of practices and beliefs carried out by the traditional Dusun community in agricultural activities can help prevent deforestation, forest burning, and the use of chemical fertilizers and pesticides. This can indirectly help the government’s efforts in preserving the environment. The Dusun community that practices a collective culture also successfully applies the value of mogitatabang when working in agriculture. These values should be applied among the current generation as a medium for building a cooperative and collaborative human model, apart from being able to preserve cultural heritage.Full text: PDF